(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Youth education is one of the most important and basic tasks of our society. The importance of this task lies in the fact that before independence, our people, especially our youth, were brought up on the basis of a single dominant ideology and were forced to mature in the spirit of indifference, dependence, muteness, and subordination to the homeland, the nation, and the future.